Association of coronary plaque composition and arterial remodelling: a virtual histology analysis by intravascular ultrasound. Issue 8 (7th November 2006) - Surmely, Jean-François; Nasu, Kenya; Fujita, Hiroshi; Terashima, Mitsuyasu; Matsubara, Tetsuo; Tsuchikane, Etsuo; Ehara, Mariko; Kinoshita, Yoshihisa; Takeda, Yoshihiro; Tanaka, Nobuyoshi; Katoh, Osama; Suzuki, Takahiko
Abstract : Background: Conflicting data have been reported about the correlation between plaque composition assessed by virtual histology (VH) and remodelling index (RI). Aim: To evaluate, in a larger patient population, the relationship between plaque morphology obtained by VH and arterial remodelling. Methods and results: VH intravascular ultrasound was performed on 95 non-bifurcation native significant lesions (>75% stenosis) in 85 patients. Positive remodelling (defined as RI ⩾1.05) was present in 28 lesions, whereas intermediate/negative remodelling (RI <1.05) was present in 67 lesions. Compared with intermediate/negative remodelling, positive remodelling was associated with an increased frequency of patients with acute coronary syndrome (n = 13 (52%) vs n = 15 (25%); p = 0.017), and with a greater plaque burden (mean (SD) 78.3 (6.3)% vs 73.2 (6.8)%, p = 0.001). At the minimal lumen site, necrotic core was significantly smaller in lesions with positive remodelling (median (interquartile range) 5.0% (2.2–11.0%)) than in lesions with intermediate/negative remodelling (median (interquartile range) 9.0% (4.0–16.0%); p = 0.048). No differences were observed in the rate of thin-cap fibroatheroma or in the presence of multiple necrotic core layers, and there were no statistical differences for fibrous, fibro fatty and dense calcium percent plaque area at the minimum lumen diameter (MLD), or for the entire lesion length between both groups. Conclusions: In vivo VH analysis shows that lesions with positive remodelling have statistically less necrotic core percent area at the MLD site compared with intermediate/negative remodelling lesions.